'Active play may be lots of fun, but it's certainly not frivolous': the emergence of active play as a health practice in Canadian public health. Issue 8 (11th June 2014) - Alexander, Stephanie A.; Frohlich, Katherine L.; Fusco, Caroline
Abstract In the context of what has been termed a childhood obesity epidemic, public health institutions have recently begun to promote active play as a means of addressing childhood obesity, thus advancing play for health. Drawing on Foucault, this article problematises the way that children's play is being taken up as a health practice and further considers some of the effects this may have for children. Six Canadian public health websites were examined, from which 150 documents addressing children's health, physical activity, obesity, leisure activities and play were selected and coded deductively (theoretical themes) and inductively (emerging themes). Bacchi's (2009) question‐posing approach to critical discourse analysis deepened our analysis of dominant narratives. Our findings suggest that several taken‐for‐granted assumptions and practices underlie this discourse: (i) play is viewed as a productive activity legitimises it as a health practice; (ii) tropes of 'fun' and 'pleasure' are drawn on to promote physical activity; (iii) children are encouraged to self‐govern their leisure time to promote health. We underscore the need to recognise this discourse as contingent and as only one of many ways of conceptualising children's leisure activities and their health and social lives more generally.